Carceral fantasies : cinema and prison in early twentieth- century America / Alison Griffiths - Grifﬁths, Alison
A groundbreaking contribution to the study of nontheatrical film exhibition, Carceral Fantasies tells the little-known story of how cinema found a home in the U.S. penitentiary system and how the prison emerged as a setting and narrative trope in modern cinema. Focusing on films shown in prisons before 1935, Alison Griffiths explores the unique experience of viewing cinema while incarcerated and the complex cultural roots of cinematic renderings of prison life.